ANALISIS IMPLEMENTASI PENDIDIKAN KARAKTER DALAM PEMBELAJARAN PENDIDIKAN PANCASILA DI SEKOLAH DASAR - Ardelia Sabila; Asep Sahrul Gunawan (STKIP Subang, 2026)
The development of the globalization era has negatively impacted students character, therefore, character education is a crucial aspect that must be integrated into the learning process. One subject that plays a strategic role in instilling character values is pancasila education. This study aims to analyze the implementation of character education, as well as the obstacles and solutions in implementing character education in pancasila education. The method used is a Literatur Study by reviewing 14 national journal articles indexed by SINTA and 2 relevant reference books. The results of the study indicate that pancasila education in effective in shaping the character of elementary school students. However, several obstacles to implementing character education in elementary school exist, including the diversity of students abilities in understanding the material, limited learning media, and lack of communication between teachers and parents. Therefore, a more effective learning approach and family support are needed to ensure the successful and sustainable implementation of character education in pancasila education.